2010
DOI: 10.1007/s10103-010-0767-z
|View full text |Cite
|
Sign up to set email alerts
|

Effect of low fluency dentin conditioning on tensile bond strength of composite bonded to Er:YAG laser-prepared dentin: a preliminary study

Abstract: Several studies in the literature have previously shown that the bond strength of a composite bonded to dentin is almost equivalent as when dentin is prepared by either bur or Er:YAG laser. The aim of this preliminary study is to assess the hypothesis that dentin conditioning at low fluency by means of Er:YAG laser can improve the value of adhesion of composites resin to dentin. Sixty surfaces of caries-free human third molars extracted for orthodontic purposes were randomly divided into five groups of 12 teet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
25
0
17

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(44 citation statements)
references
References 16 publications
2
25
0
17
Order By: Relevance
“…This technique provides a more comfortable treatment for the patient by reducing stress and vibration and allows ultra-conservative cavity preparations [7] as claimed in modern dentistry.…”
Section: Introductionmentioning
confidence: 99%
“…This technique provides a more comfortable treatment for the patient by reducing stress and vibration and allows ultra-conservative cavity preparations [7] as claimed in modern dentistry.…”
Section: Introductionmentioning
confidence: 99%
“…These cracks result from the increased pressure in the dentin subsurface due to water vaporization and subsequent ejection of organic material due to the ablation process [27]. When using a 50-μs pulse duration, fewer microcracks were expected [7,15]. It is important to note that these findings do not seem to compromise the long-term results of BS and NdHL.…”
Section: Discussionmentioning
confidence: 94%
“…These parameters were selected based on other studies [7,20] that revealed satisfactory results using an energy density of 13.33 J/cm 2 (laser 1). The results of those studies suggested the need to test the effectiveness of even lower energy densities for pretreating dentin prior to adhesive procedures; therefore, an energy density of 8.33 J/ cm 2 (laser 2) was also chosen [7]. Both Er:YAG laser surface pretreatment protocols in both substrates did not alter the BS of CF for both evaluation periods tested.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations